Effect of chemical fertilizers and biofertilizers on rajmash (Phaseolus vulgaris) in cold desert region of North-western Himalayas - SINGH, J; CHAUDHARY, D R (The Indian Journal of Agricultural Sciences, 2018)
A field experiment was conducted to study the combined effect of chemical fertilizers and biofertilizers on growth, yield and economics of rajmash (Phaseolus vulgaris L.) at Highland Agricultural Research and Extension Centre, Kukumseri during two consecutive summer seasons of 2012 and 2013. The experiment was laid out in randomized block design with nine treatments and replicated thrice. Growth, yield attributes and yield were significantly increased with combined application of chemical fertilizers and biofertilizers. The tallest plants were recorded in T6 (N60 P60 K30 + seed inoculated with Rhizobium and phosphate solubilizing bacteria) while the shortest plants were in T9(N0 P0 K0 BF0 ). Significantly higher values of pod length, seeds per pod, seed index, seed yield and straw yield were also recorded in T6 . Maximum mean value of dry matter efficiency and harvest index was observed in T7 (N0 P60 K30 + seed inoculated with Rhizobium and PSB) while maximum mean value of unit area efficiency, net returns and B:C ratio was in T. Based on the mean value of two years, T6 resulted in 81.11, 77.48, 77.49, 172.05 and 65.32% higher dry matter production, unit area efficiency, seed yield, net returns and B:C ratio, respectively as compared to control treatment (T9 ). Maximum mean profitability (Rupees1477/ha/day) was also recorded in T6 . Integrated application of 60 kg N, 60 kg P2 O5 and 30 kg K2 O/ha along with seed inoculation with Rhizobium and PSB proved to be the best treatment for higher productivity and profitability of rajmash crop in cold desert region of North-western Himalayas.